Pengaruh Electronic Word of Mouth dan Video Content Marketing Terhadap Niat Beli Produk Erigo di Semarang - Faisal Dwi Eksanto; Alimuddin Rizal (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study was conducted to analyze the effects of electronic word of mouth and video content marketing on purchase intention. The respondents of this study were customers of Erigo products in Semarang, totaling 162 individuals. The sampling technique used was purposive sampling, and the data were analyzed using PLS SEM (Partial Least Squares Structural Equation Modeling). The results of this study indicate that purchase intention is positively and significantly influenced by electronic word of mouth and video content marketing. The most dominant influence on purchase intention comes from the e-WOM variable.